Gender and indentity aspects in costume of different time periods and peoples - Yu. L. Gerasimova; O. A. Kirillova (Омский научный вестник: Серия "Общество. История. Современность")
Comparative analysis of men’s and women’s wardrobe is done. A study of changes is in the design and form creation. The expansion of the range of clothing is analyzed. The analysis of similarities and differences in men’s and women’s clothing in the period of the first civilizationsis done. Analysis functions of costume in certain historical periods is done. Analysis functions of costume in cultures certain peoples is done. Comparison of gender characteristics of clothing based on the lifestyle of pagans and christians is given. There is considered the relationships of gender and clothing. It is indirectly affected by the question of the relationship of religion to clothing and gender. There are considered the features of the historical costume